Probiotic Supplementation as an Alternative to Antibiotics in Bovine Sperm Cryopreservation: Effects on Motility, Oxidative Stress and Apoptosis - Omur, Ali Dogan; Celebi, Demet; Akarsu, Serkan Ali; Yildirim, Betul Apaydin; Ucak, Gamze; Acisu, Tutku Can; Hussain, Tarique (Wiley, 2026)
This study aimed to evaluate the effects of probiotic supplementation on bovine sperm cryopreservation by assessing post-thaw spermatological and biochemical parameters. Twenty-four ejaculations were collected from four Simmental bulls using the artificial vagina method. Ejaculates exhibiting over 70% motility were pooled to eliminate individual variations and allocated into five experimental groups: antibiotic-free control group, antibiotic group, LA, BL and LR groups, respectively. Three probiotic strains, Lactobacillus rhamnosus (LR), Lactobacillus acidophilus (LA) and Bifidobacterium longum (BL), were incorporated into a Tris egg yolk-based semen extender at a concentration of 10(9) CFU/mL. Following dilution, samples were equilibrated and subsequently stored in liquid nitrogen. Post-thaw evaluations were conducted for sperm motility and kinematic parameters using CASA, hypo-osmotic swelling test, fluorescent staining for chromatin integrity, acrosomal integrity and mitochondrial membrane potential, as well as oxidative stress biomarkers. Additionally, apoptosis and metabolism related proteins were quantified by ELISA. The results exhibited that probiotic treated groups had significantly higher total and progressive motility as compared with controls (p < 0.001). In comparison with the control group, BL supplementation showed significantly reduced lipid peroxidation and increased antioxidant enzyme activities, along with lowered TGF-beta and Caspase-3 levels, indicating attenuated oxidative stress and apoptotic signalling (p < 0.001). In contrast with the control group, LR supplementation resulted in elevated MDA and apoptosis-related markers, suggesting strain specific pro-oxidative effects (p < 0.001). There were no significant differences observed in STAR or ATP synthase levels across the treatments. Altogether, the results exhibited that strains of probiotics, particularly BL, have the potential to serve as an alternative to antibiotics in bovine semen cryopreservation. Nevertheless, strain-dependent responses and limitations, especially with respect to DNA integrity, require further investigation.
Keywords: alternative to antibiotics; bulls; cryobiology; probiotic strains; sperm quality